Synthesis and Biological Evaluation of Novel γ-Alkylidene Butenolides - Gai-Zhi Liu; Yan-Bin Guan; Ya Wu; Hong-Min Liu (Journal of Chemistry)
Three new series of 4-substituted-5-alkylidene-2,5-dihydrofuran-2-ones were synthesized. The in vitro activity test results showed that some of them exhibited good antibacterial and cytotoxic activities. Among them compound 5c showed the most potent antibacterial activity against Escherichia coli with the MIC value of 20.00 μg/mL. Compound 9c showed good cytotoxic activity against Ec9706 cells with IC50 value of 19.39 μM, better than that of the reference compound fluorouracil (IC50=37.74 μM).